2013
DOI: 10.1590/s1517-86922013000100015
|View full text |Cite
|
Sign up to set email alerts
|

Evidências de que um protocolo de atividade física pode reduzir a contagem de leucócitos sinoviais de ratos artríticos

Abstract: ABSTRACTintroduction: physical activity is thought to be beneficial to arthritis, delaying disability and/or improving joint function. in vivo studies using experimental models of arthritis may provide useful information about such benefits. Objective: The aim of the present study was to evaluate the effects of the low-intensity exercise on a model of CFA-induced arthritis in rats. Methods: Articular incapacitation was measured by the paw elevation time in 1-min periods of stimulated walk. Edema was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…In experimental models of arthritis, it has been confirmed that mechanical stress increase joint inflammation, stimulate the progression and chronicity of arthritis and structural damage [16,17,48]; besides, the mechanical stress decrease the bone quality [16]. In contrast to our findings, other studies in the AIA model have shown an anti-inflammatory effect of PE in some parameters such as synovial hyperplasia [49,50], and joint destruction [51].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In experimental models of arthritis, it has been confirmed that mechanical stress increase joint inflammation, stimulate the progression and chronicity of arthritis and structural damage [16,17,48]; besides, the mechanical stress decrease the bone quality [16]. In contrast to our findings, other studies in the AIA model have shown an anti-inflammatory effect of PE in some parameters such as synovial hyperplasia [49,50], and joint destruction [51].…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, the severity of arthritis at the starting time of PE could be definitory. Studies in the AIA model that started the PE at the pre-arthritic stage [49,50] showed beneficial results. However, we started the PE at an arthritic stage because we think this scenario is more representative of RA patients.…”
Section: Discussionmentioning
confidence: 99%